Types of entrepreneurs in small hotels in Slovenia - Zupan, Saša (Academica turistica, 2017)
Entrepreneurship is associated mostly with establishing of new ventures, mainly of small and medium size companies (smes). It is linked closely with the entrepreneur: The key person who plays the key role in the entrepreneurial process. In theory, different criteria have been used in the past to identify the typology of entrepreneurs, e.g. the period of entrepreneurial activity, their economic or non-economic goals, etc. (Dunkelberg, Moore, Scott, & Stull, 2013; Dincer, Yildirim & Dil, 2011; Hisrich, Peters, & Shepherd, 2010; Glas, 2002; Smith & Miner, 1983). The main purpose of this paper is (a) To the identify typology of entrepreneurs in Small Hotels (sh) in Slovenia and (b) To compare the results with findings of similar studies in existing literature (Page & Connell, 2014; Lee-Ross & Lashley, 2009). Empirical research was conducted in Slovenia in 2014 and 2015. The data were collected from shentrepreneurs and shDirectors (a) By conducting 62 semi-structured interviews and (b) By analysing 44 questionnaires filled in by shentrepreneurs. We analysed data from interviews using qualitative methods (interpretation, comparison, grouping, quantification). The numerical data were processed and analysed by using multiple statistical tools (factor analysis, hierarchical classification, Ward%s method). shentrepreneurs in Slovenia share certain typology characteristics with their colleagues in the hospitality business abroad; however, there are less lifestyle entrepreneurs in the Slovene hospitality business than expected (due to comparison with findings in existing literature). This is the first research of entrepreneurial typology in the hospitality business in Slovenia. It offers a clear insight into certain business orientations of hospitality entrepreneurs and, consequently, gives some explanation about tourism entrepreneurship in Slovenia
Keywords: hoteli; hotelirstvo; mala podjetja; podjetništvo; Slovenia; Slovenija